27=6b

Simple and best practice solution for 27=6b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27=6b equation:


Simplifying
27 = 6b

Solving
27 = 6b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-6b' to each side of the equation.
27 + -6b = 6b + -6b

Combine like terms: 6b + -6b = 0
27 + -6b = 0

Add '-27' to each side of the equation.
27 + -27 + -6b = 0 + -27

Combine like terms: 27 + -27 = 0
0 + -6b = 0 + -27
-6b = 0 + -27

Combine like terms: 0 + -27 = -27
-6b = -27

Divide each side by '-6'.
b = 4.5

Simplifying
b = 4.5

See similar equations:

| -5.5x-20=5.5x+24 | | ^3-2x/^4x=2 | | 3860+x=4135 | | 2(2x-6)=14 | | 5+(8)n=29 | | 9c+5=18-4c | | x^2+15x=8x+60 | | 6(r+8)=18 | | 14-y= | | 2y+24=3x | | 6p+8= | | 5+(-4)n=25 | | p/2−2=p-8 | | 13u=63+4u | | 20g+24h= | | -10+7y=x | | 4x+2f(x)=9 | | 18-y=5y | | 3g+1=7g-19 | | 100-83.4=16.6 | | 5(4m+2)=18 | | 7x^4y-9x^3y+3x^2y^5=0 | | 2x-x-9=0 | | 5y+3xy+2y= | | x/-23 | | -8=-(x-8) | | 20m=8 | | 49a^7b^4-84a^5b^4=0 | | S=p+I | | 2y/8y^(n-1) | | 6x-16=-22+6x | | 1=3.33 |

Equations solver categories